The Effect of Discovery Learning Model Using Concept Map and Computer Animation on Student Learning Outcomes in Hydrocarbon Material - Anita Debora Simangunsong (IJECA (International Journal of Education and Curriculum Application), 2020)
This study aims to determine the effect of discovery learning with concept maps and computer animation media on chemistry learning outcomes on the subject of hydrocarbons. The sample in this study was students of Mathematics Education semester 1 HKBP Nommensen Pematangsiantar University odd semester of the 2019/2020 school year. The instrument used in data collection is a validated test instrument. The data obtained were tested with a comparative study using the two-party t test. From the normalized gain data, a large increase in student learning outcomes by using discovery learning teaching with concept maps and computer animation media was 54% of the experimental class I and 70% of the experimental class II. The magnitude of the difference in the increase in student learning outcomes is 16%. Based on the results of hypothesis testing, obtained tcount> ttable is 5.56> 1.6671 at a significant level α = 0.05. This means that H0 is rejected and Ha is accepted, which states that there are significant differences in student learning outcomes by applying discovery learning using concept maps and computer animation on hydrocarbon material.